Effectiveness of promotional elements towards society awareness of E-Kasih program done by Jempol District and Land Office / Khairunnisa Udin - Udin, Khairunnisa (Faculty of Business and Management, 2014)
Living standards of Malaysians have improved significantly over the past 50 years. Today less than 4% of Malaysians live in poverty. Our aspiration is to eradicate extreme poverty and reduce the overall poverty rate, thus managing the polarity between the rich and the poor. Jempol District and Land Office or Pejabat Daerah dan Tanah Jempol (PDTJ) Negeri Sembilan were implemented the E-Kasih program which is designed to provide a single database holding all relevant information including citizens’ profiles. Therefore, there are a few program under the E-Kasih were implemented to the society.